Weight gain in pregnancy and its correlation with birth weight of infants in ‎women Who reffered to obstetric wards of Hajar hospital in Shahrekord - masoumeh delaram; nasrin akbari (Guilan University of Medical Sciences, 2006)
Introduction: Birth weight is one of the main determinators for somatic and mental growth in ‎infants and it is an important symptom of intrauterine growth. Thus recognition of factors that ‎affects the low birth weight and elimination of them is important.‎ Objective: This study was designed to detect the weight gain in pregnancy and its correlation ‎with birth weight of infants.‎ Methods: Six hundred pregnant women were selected randomly from those reffered to ‎delivery room in Hajar hospital. Data was collected by a questionnaire using interview with ‎mothers, prenatal and infants records. We used similar scale to measure the mothers and ‎infants weight. Age of mother less than ‎‏18‏‎ and more than ‎‏35‏‎, gestational age less than ‎‏37‏‎ ‎weeks, twin pregnancy, history of abortion and intrauterine fetal death, smoking drinking of ‎alcohol and medical history of diseases in mother, were excluded. Data were analyzed by ‎SPSS(t- test, chi-square test and one way ANOVA test).‎ Results: The mean weight gain in pregnancy was ‎‏11.4‏‎ ‎ ‎ ‎‏3.6‏‎ kg. This mean was increased ‎with increase in number of delivery (P=‎‏0.01‏‎), mothers education level (P=‎‏0.01‏‎) and also in ‎CS (P=‎‏0.006‏‎). The mean birth weight was ‎‏3179‏‎.‎‏08‏‎ ‎ ‏433.10‏‎ only ‎‏7.3‏‎ % of infants had birth ‎weight less than ‎‏2500‏g. There was a significant relationship between birth weight and ‎multiparty, mothers education level, weight at beginning of pregnancy, weight gain during ‎pregnancy and sex of infant (P=‎‏0.05‏‎).‎ But in regression statistics, only weight at beginning of pregnancy, increase weight gain ‎during pregnancy and mothers level of education were significant predictors of infants birth ‎weight.‎ Conclusion: Results of this study shows the importance of mothers weight in beginning and ‎during pregnancy as criteria for identifying mothers who are at risk of giving birth to low birth ‎weight infants. After identifying these mothers, better and more care can be given and also ‎give them necessary information.‎